Reproducible X-Ray Projection Geometry in Endodontic Practice - Ghalamkarpour, Zohre; Ashraf, Hengameh; Mozayani, Mohammad Ali; Yazdani, Ramin (Iranian Endodontic Journal, 2008)
INTRODUCTION: Clinical application of radiography in endodontic practice is affected by reproducibility in the orientation of the x-ray source, image receptor and object. The inability of dentists to locate intra oral films or sensors in appropriate positions in different cases can cause complications in the performance of endodontic therapy. Commercially available film holder (endoray) and conventional imaging methods seem to be insufficient and difficult to perform. The purpose of this investigation was to develop a novel and easily performed device for endodontic radiography and to asses its reproducibility and accuracy in vitro. MATERIALS AND METHODS: The present work surveys and evaluates the design steps of a newly constructed film holder with modified bite block and a beam guiding device, in an attempt to perform a diagnostic study. References wires and balls were attached on the film holder and to the alveolar crest of maxillary molar region inserted in the conventional phantom for measuring the projection errors relative to the film holder and repositioning .One hundred and twenty radiographs of a conventional phantom were taken by one of the authors and by two dental students using the novel device and Endoray. RESULTS: The %95 CI for precision of radiologist and one of the students was less than 8 (7.313 ± 0.1989) .The %95 CI for precision of the other student was less than 12 (10.941 ± 0.4217). There was no significant difference (p= 0.679), regarding the interoperator precision, between radiologist and first student. There was significant difference between second student and the others (p<0.05). No significant difference was noted between the radiographs achieved by the Endoray and new device. CONCLUSION: The novel device appears to be a potential means of obtaining reproducible radiographs in endodontic practice. Further research is needed however, to study in vivo aspects, reproducibility and accuracy.